Focus groups theory and practice - Stewart, David W.; Shamdasani, Prem N.; Rook, Dennis W. (Thousand Oaks, Calif. ; London : SAGE, 2007)
Stressing the interaction of the moderator and group as well as the mechanics of designing, conducting and interpreting the outcome of focus groups, this work provides a systematic treatment of focus group interviews within the context of social science research and theory.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: elektronické knihy; electronic books; Focus groups; Social sciences -- Research -- Methodology; Social groups